(3ebGeGJ GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3ef ebGeI GdYjO bhdg(B:- (3CNHQ gGTe Hf GdbGSe bGd(B: (3YLJ Edi bdYI eUQ, ai jhe YjO aWQ s
(3BNQgG (B:s
(3ef GdebGeI GdKGfjI hGdYTQjf, hgj GdebGeI GdcdGLjI ai GdCSFdI GdfGLjI , bhdg aEf Hjfg hHjf GdLhGH MLGH, hGddg Gdehab BNQgG s
(3HgG fXGe GdJYbjHIs
(3YOOgG GKfJGf hYTQhfs
(3HOGNdgG Jedc SfI (B1255 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs